An assessment of the clinical competencies of radiologic technology educators in the Philippines: basis for proposed clinical enchancement program / Cheyen Estores Molon. - Molon, Cheyen E. (2012)
Utilizing the descriptive method of research, and anchored on the theoretical framework for clinical assessment by Miller (1990), this study focused on the assessment of the clinical competencies of the Radiologic Technology (RT) educators in the Philippines. Assessment was based on specific subject/s taught pertaining to diagnostic and therapeutic modalities. Respondents were RT educators and RT interns. Data were obtained using a self-made questionnaire. Data gathered were treated using percentage frequency, mean, standard deviation, Kruskal Wallis H test, and independent‘s t-test. Findings showed that majority of RT educators were holders of a bachelor‘s degree, not working with other institutions, with full-time status, has a teaching load of 18 units and above, and teaching more than one (1) subject. Majority attributed their clinical experience to internship training for BSRT and clinical training in hospitals. The faculty development program focused on financial support for convention. Self-assessment of educators revealed that majority knows the tasks on the different modalities, have been performing it, and have very high clinical competency in Nuclear Medicine, Radiologic Contrast Examination, Radiographic Technique and Film Processing/Analysis, CT Scan, Ultrasound, Radiation Therapy, Interventional Radiology, Radiographic Positioning and Radiologic Procedures, and MRI; in clinical experience and faculty development program. RT interns revealed that RT educators have high clinical competency in Radiographic Positioning and Radiologic Procedures, Nuclear Medicine followed by Radiologic Contrast Examination and Radiographic Technique and Film Processing/Analysis. Moderate clinical competency was noted in CT Scan, Ultrasound, Interventional Radiology, Radiation Therapy, and MRI. Comparison of the assessment of the clinical competency shows that, the p-values that obtained higher than 0.05 level of significance, which means that the RT educators‘ clinical competency in the nine (9) areas of modalities were the same regardless of their educational attainment and number of subject/s taught, other institutional connection except in Interventional Radiology, teaching load except for MRI and Interventional Radiology, and work status except for Radiologic Contrast Examination, Interventional Radiology, and Nuclear Medicine. Significant differences in the clinical competencies of RT educators were noted in the following areas, namely: (a) very high clinical competency in interventional radiology was observed to those faculty members with parttime employment status, with less than 18 units of teaching load, and are connected in other institutions like hospital, (b) very high clinical competency in Nuclear Medicine and Radiologic Contrast Examination was noted from RT educators with full-time employment status, and (c) RT educators with less than 18 units of teaching load have very high clinical competency in MRI. In terms of clinical experiences, clinical competency significantly differs in: (a) work-related clinical experience in CT Scan, MRI, Radiographic Technique and Film Processing/Analysis, and Ultrasound, (b) clinical training in hospital for Radiologic Contrast Examination and MRI, and (c) internship training program for BSRT in Radiographic Positioning and Radiologic Procedure and Interventional Radiology. In terms of faculty development program, significant differences in the clinical competency of RT educator was noted in sponsored in house seminar for Radiographic Positioning and Radiologic Procedures, financial support for conventions for Interventional Radiology, and provision for post graduate education in Radiographic Positioning and Radiologic Procedures and Radiation Therapy. The author recommends: to provide an intensive hospital training; provide post-graduate education; subsidize attendance in seminars, conferences, and other training programs; develop and administer an annual faculty survey to compile demographics and identify trends in faculty development needs; incorporate flexible scheduling; consider the clinical enhancement program (CEP); and periodical re-evaluation of the CEP.